The teachers initial training and the insertion in scholastic context: a bibliometrics study - Luciana Cristina Cardoso; Daniel Mill; Maria Iolanda Monteiro (Universidade Federal de Santa Catarina, 2017)
From the perspective that the teaching career is lifelong built and that the initial formation is shown as a singular moment in the process, this work seeks to reveal the representativeness of the initial formation thematic linked to teachers' teaching-in-context experiences in Brazilian research. Therefore, 3,468 theses from Education Post Graduation Programs cataloged in the basis of the Novo Horizonte Group (Study and Research Group on Innovation in Education, Technology and Languages from the Federal University of São Carlos - UFSCar) have been taken as object of study. The bibliometric research reveals that the initial formation, mediated by experiences in school settings, is present in 11 theses from a total of 3,468 works. The analyzes indicate that, although there are relevant studies to the field, the in-context formation (marked by experiences that go beyond the Teaching Practice and Supervised Internship), is not representatively inserted in the academic scenario. Among some important contributions to the line of teacher formation, the study also indicated that researches addressed institutional formation programs and that in none of them it was possible to identify the creation of a formation space, characterized also as research intervention, suggesting a possible lack of construction, implementation and analysis of new programs, such as formation spaces designed under the hybrid or virtual perspective.